(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
The COVID-19 crisis confronted states with the challenge of finding an immediate balance between public health measures and the principles of the rule of law. The rapid spread of the virus associated with the severe consequences on human health and life required prompt action, without the necessary scientific evidence to assess the effectiveness of the measures taken. Being faced with such a situation, numerous countries opted for drastic measures, like lock down and the restriction of some fundamental human rights and freedoms. This paper analyses the freedom of peaceful assembly during the COVID-19 pandemic in Albania, addressing the research question of whether and to what extent the response of the Albanian government to the COVID-19 pandemic was in compliance with the European Convention of Human Rights (ECHR). In this attempt, it will briefly introduce the measures taken by the Albanian government in the face of the situation and their impact. Following, it will focus on the recent decision of the Constitutional Court of Albania (D-11/21) in relation to the constitutionality of Order 633/2020 of the Ministry of Health and Social Protection which restricted the right of assembly. It will also analyze the extensively-discussed Order 633/2020 in the light of the ECHR and EU standards. The paper concludes that the measures taken by the Ministry of Health and Social Protection of Albanian lacked clarity on ratio legis and most importantly, information on how these measures would be implemented and to what extent they would restrict human rights.